Function of Moringa oleifera Lamk Leaf Extract as an Antiseptic for Pseudomonas aeruginosa and Staphylococcus aureus using Percentage Kill Method - Kiranasari, Ariyani; Tjampakasari, Conny Riana; Putri, Mariza Nabila; Pratama, Vanessa Maritza (Jurnal Kedokteran Meditek, 2024)
Moringa oleifera Lamk leaf extract has an antimicrobial properties especially against fungal, parasite, Gram positive and negative bacteria by inhibiting DNA synthesis and metabolism an damaging cell walls. The aim of this study was to determine whether M. oleifera Lamk leaf extract is effective as an antiseptic against P. aeruginosa and S. aureus bacteria. Percentage Kill was used in the study to determine the percentage of  bacteria death after contact with M. oleifera Lamk leaf extract in the 1st, 2nd and 5th minutes against the control and treatment simultaneously. The test is considered to meet the standard if each contact gives a result of ≥90%. For  discovered percentage kill to P. aeruginosa bacteria in the 1st, 2nd and 5th minutes each test showed a yield of 27.12%. , 47.01%, 57.7%. In the third time of  P. aeruginosa did not reach the standard. Whereas in S. aureus bacteria, each test showed a yield of 92.36%, 95.58% and 96.45%, where it was seen that all results reach  the standards criteria of ≥90%.  M. oleifera Lamk leaf extract was not effective in eliminating P. aeruginosa for all contacts because the standard value was below 90%. Whereas for S. aureus bacteria, M. oleifera Lamk leaf extract was very effective in eliminating bacteria for all contact times ≥90% with the highest value at the 5th minutes (96.45%).